The existence of 'Urf in the Resolution of Marriage Disputes in Islamic Law: A Living Law Perspective - Luthfi, Muhammad; Fajrin, Yaris Adhial; Bachtiar, Hasnan (Magister of Law, Faculty of Law, University of Mataram, 2024)
‘Urf or customary law is a law that lives, develops, and is implemented by society. In the practice of marital disputes, people tend to implement customary law, or 'urf, first before resolving them through formal mechanisms regulated in statutory regulations. This research aims to analyze 'urf or customary law in marriage disputes from the living law aspect. This research is normative legal research that prioritizes conceptual and statutory approaches. The research results confirm that the position and existence of 'urf or customary law in marriage disputes is permissible as long as it does not conflict with Islamic law, guarantees benefits, and contributes to the successful implementation of Islamic law. Legal efforts to resolve marriage disputes through 'urf are viewed from a living law perspective because, as a law that applies and its value is appreciated by society, in marriage disputes, the role of 'urf or customary law is important to bring justice to the parties in dispute. Apart from that, legal efforts to resolve marital disputes through 'urf from a living law perspective can also be the first attempt to resolve marital disputes, and if efforts through 'urf or customary law are not successful, then efforts can be made to resolve them through procedures in the KHI and statutory regulations.